Contemporary Iran - "Wilber, Donald N." (London, 1963)
This book covers the following topics The Land, the People, and the Natural Resources;Patterns from the Past The Continuity of History / The Continuity of Culture / The Continuity of Social Patterns; Challenges to Patterns of Continuity;The Turbulent Present Three Challenges to the Historical Past / Institutions of Authority / Organizations and Forces Challenging Authority / Institutions and Programs Contributing to Stability and Progress / External Forces Operating on the Iranian Scene ;Challenges of the Future Possible Developments in the Monarchy, the Government, and Politics; Attitudes of Society, Economic Prospects, and Foreign Relations etc.
Keywords: Politics & Govt